Knowledge and systems sciences : 20th International Symposium, KSS 2019, Da Nang, Vietnam, November 29-December 1, 2019, Proceedings /: 20th International Symposium, KSS 2019, Da Nang, Vietnam, November 29-December 1, 2019, Proceedings. (2019) - Unknown
No abstract available